Oxidative stress and mitochondrial adaptive shift during pituitary tumoral growth - Sabatino, María Eugenia (2018)
The cellular transformation of normal functional cells to neoplastic ones implies alterations in the cellular metabolism and mitochondrial function in order to provide the bioenergetics and growth requirements for tumour growth progression. Currently, the mitochondrial physiology and dynamic shift during pituitary tumour development are not well understood. Pituitary tumours present endocrine neoplastic benign growth which, in previous reports, we had shown that in addition to increased proliferation, these tumours were also characterized by cellular senescence signs with no indication of apoptosis. Here, we show clear evidence of oxidative stress in pituitary cells, accompanied by bigger and round mitochondria during tumour development, associated with augmented biogenesis and an increased fusion process. An activation of the Nrf2 stress response pathway together with the attenuation of the oxidative damage signs occurring during tumour development were also observed which will probably provide survival advantages to the pituitary cells. These neoplasms also presented a progressive increase in lactate production, suggesting a metabolic shift towards glycolysis metabolism. These findings might imply an oxidative stress state that could impact on the pathogenesis of pituitary tumours. These data may also reflect that pituitary cells can modulate their metabolism to adapt to different energy requirements and signalling events in a pathophysiological situation to obtain protection from damage and enhance their survival chances. Thus, we suggest that mitochondria function, oxidative stress or damage might play a critical role in pituitary tumour progression.